A Regulatory Network of Heat Shock Modules-Photosynthesis-Redox Systems in Response to Cold Stress Across a Latitudinal Gradient in Bermudagrass - Chen, Minghui; Gan, Lu; Zhang, Jingxue; Shen, Yu; Qian, Jin; Han, Mengli; Zhang, Chuanjie; Fan, Jibiao; Sun, Shengnan; Yan, Xuebing (Frontiers in Plant Science, 2021)
Bermudagrass (Cynodon dactylon Pers.) is a wild Poaceae turfgrass with various genotypes and phenotypes. In this study, 16 wild bermudagrass germplasms were collected from 16 different sites along latitudinal gradients, and different temperature treatments were compiled and used for physiological and transcriptome analysis. To explore the correlation between the key differentially expressed genes and physiological indicators, a total of 14,654 DEGs were integrated from the comparison of different temperature treatments and used for weighted gene co-expression network analysis. Through comparative transcriptome analysis and gene annotation, the results showed that differential gene expression profiles in networks are associated with the plant growth, photosystem, redox system, and transcriptional regulation to cold stress in bermudagrass. In particular, genes encoding HSP70/90 and HsfA3/A8 are not only regulated by temperature stress, but also directly or indirectly interplay with the processes of peroxide scavenging and chlorophyll synthesis under cold stress. Besides, through a weight evaluation analysis of various physiological indexes, we identified an accession of wild bermudagrass with relatively strong cold resistance. These results provide important clues and resources to further study the responses to low-temperature stress in bermudagrass.